Análisis energético de la incidencia de la capacidad de la batería de elevado voltaje en el consumo de combustible del vehículo Toyota Prius C. Diseño del sistema de control de energía para elevar la autonomía de desplazamiento del vehículo plug-in Toyota Prius C durante el año 2016. - López Guzmán, Diego Wladimir (2017)
The research work considers the incursion and influence that has been generating the hybrid vehicle in the country. An important search was made for reliable bibliographic information to have the fundamental criterion of the technology used in the high voltage batteries and to determine the incidence of the load capacity in relation to fossil fuel consumption in the Toyota Prius C vehicle, developing The proposed design and implementation of an additional electric power control plug-in system based on the recycling of the Toyota Highlander vehicle battery that was appropriate for the research developed in that each pack has a nominal value of 9.6V and 6.5A / H, placed in 2 series of 15 cells, giving a total value of 144V and 6.5 A / h, is recharged by 110 volts home network, installed in the back, optimizing the space as much as possible, is in parallel With the original high-voltage battery supplying the power and making the internal combustion engine stay longer off, without losing performance inside the passenger compartment. The proposal was xxivalidated with the use of state-of-the-art equipment with which it was determined the elevation of the autonomy in the displacement of the hybrid vehicle in elevation of the autonomy in 30 km in city and 25 km in highway with the respective decrease of the consumption Of gasoline and therefore reduction of environmental pollution.